150k views
2 votes
Solve for x.

d(-3+x)=kx+9

Solve for x. d(-3+x)=kx+9-example-1
User Yoav T
by
5.7k points

2 Answers

5 votes

Answer:

x = -9 / (2d+k)

Explanation:

d(-3x+x) = kx+9

-3dx + dx = kx+9

-3dx + dx - kx = 9

x(-3d+d-k) = 9

x (-2d-k)= 9

x [-(2d+k)]=9

x = -9 / (2d+k)

User Berline
by
5.6k points
3 votes

Answer:

The value of the provide equation for x is
x=(9+3d)/(d-k).

Explanation:

Consider the provided equation.


d(-3+x)=kx+9

We need to solve the equation for x.

Use the distributive property:
a(b+c)=ab+ac


-3d+xd=kx+9

Subtract kx from both sides.


-3d+xd-kx=kx-kx+9


-3d+xd-kx=9

Add 3d both sides.


-3d+3d+xd-kx=9+3d


xd-kx=9+3d

Take x common from left side.


x(d-k)=9+3d

Divide both the sides by d-k.


(x(d-k))/(d-k)=(9+3d)/(d-k)


x=(9+3d)/(d-k)

Hence, the value of the provide equation for x is
x=(9+3d)/(d-k).

User Overblade
by
5.5k points